Strengthening the Community Economy through Empowerment Mother House Ladder in Village Lako Akelamo Regency West Halmahera, North Maluku Province - Runtunuwu, Prince; Husen, Amran (Edujavare Publishing, 2024)
Fish is the biggest asset in Lako Akelamo Village, West Halmahera Regency . Since Lako Akelamo Village was formed, the majority of villagers work as fishermen due to the abundance of fish resources in Lako Akelamo Village. This is proven through an interview with the Department of Food Security, Agriculture and Fisheries Unit 1 which stated that in the past two years, more precisely in 2019-2022, Sahu was one of the contributors to the largest fish catch in North Maluku for two consecutive years. However, usually the villagers pass through the catch of fish they can usually sell directly to agents who come to the village or sell it to the markets directly. In facts, the fish caught can be processed into high-value food and become an alternatives to improve the economy and public health in general. Thus, through a program of processing fish into varied and productive food, skills can be improved so that's it becomes an economics and productive innovation for the community itself and for the village.